Pengaruh Pengalaman Usaha Terhadap Pengembangan Usaha Dan Penggunaan Informasi Akuntansi Sebagai Variabel Intervening (Kajian Empiris Pelaku Usaha Kecil dan Menengah di Medan Utara) - R Riadi (Jurnal Penelitian Medan Agama, 2020)
The activities of small and medium enterprises (UKM) are one of the business fields that can develop and be consistent in the national economy. UKM is a good place for creating productive jobs. The development and growth of SMEs is one of the crucial driving forces for economic development.  This research is a research with an associative quantitative approach he population in this study were SMEs in North Medan with a total population of 33 UKM. The data analysis technique used in this research is path analysis to answer the research hypothesis From the research that has been done, it is found that business experience has an indirect effect on business development through the use of information. Business experience without being followed by the use of accounting information cannot develop MSME businesses so it is hoped that MSME business actors will use accounting information as a first step in business development.